Enhancing agricultural sustainability with water and crop management strategies in modern irrigation and drainage networks - Seyedeh-Zohreh Hashemi; Abdullah Darzi-Naftchali; Fatemeh Karandish; Henk Ritzema; Karim Solaimani (Agricultural Water Management)
Improving global food security hinges on achieving sustainable agricultural production within independent irrigation and drainage units, considering the availability of sustainable water resources. This study investigated the potential for enhancing the sustainability of agricultural production in a modern irrigation and drainage network (TIDN) area and evaluated the network's performance under various strategies. These strategies included mulching, transitioning from traditional to drip irrigation, combining mulching with drip irrigation (IDM), and reducing the crop yield gap. Utilizing 2009–2018 data and the AquaCrop model, which was both calibrated and validated, the green and blue water footprints (GWF and BWF) of dominant crops in the region's cropping pattern were assessed. The crop cultivation was prioritized based on the total and unit unsustainable BWF. The performance of TIDN was evaluated using indicators of reliability, vulnerability, system deficiency, flexibility, and sustainability. The drip irrigation had the most significant impact on reducing BWF, while mulching was more effective in decreasing GWF. The adoption of IDM led to a total annual water savings of 382.4 m3 ha−1. The 10-year average reductions in BWF from May to August ranged from 1.7 to 3.1 MCM, with approximately 88–93 % of these savings attributed to decreased water consumption in rice fields. Mulch, drip, and IDM decreased the BWF by 3.3 %, 9.4 %, and 10.2 %, respectively, compared to current conditions. The study revealed that the expansion of rice cultivation under conventional flooding irrigation was incompatible with the sustainable blue water resources available, and replacing rice with wheat could reduce the unsustainable BWF by 95–100 %. Compared to current conditions, IDM improved network sustainability by 1.2 %, while closing the yield gap improved the indicator by 24 %. The findings suggest that combining infrastructural solutions, such as updating irrigation systems, with farm management solutions, such as reducing crop yield gaps and implementing mulching, can significantly enhance the sustainability of production in intensively agricultural areas.